Produktivitas Jamur Tiram Putih (Pleurotus Ostreatus) PadaMedia Campuran Serabut Kelapa Dan Ampas Aren - Wulandari, Kristina; , Dra. Suparti, M.Si (2017)
Coconut fibers and dregs palm contain cellulose and hemicellulose which can be used as an additional medium of white oyster mushrooms. The purpose of this research is know the effect of the mixture addition coconut fiber and dregs palm leaf in planting medium to the productivity of white oyster mushroom. And to know productivity of the most optimal white oyster mushrooms with the addition of a mixture of coconut fibers and dregs palm to the amount of fruit body and wet weight of white oyster mushroom. The type of experimental research with Randomized Design Completely Methode (RAL) of factorial pattern implemented in 2 repetitions. . Factor 1 coconut fiber: (S0) without addition, (S1) addition of 350 g, (S2) addition of 500 g. Factor 2 dregs palm: (A0) without addition, (A1) addition of 125 g, (A2) addition of 150 g, (A3) addition of 175 g. The results of this research were obtained (1) the addition of coconut fiber and dregs palm affect the number of fruit body (19 fruit) and the weight of white oyster mushroom (180 g). (2) The productivity of white oyster mushroom is the most optimal on the number fruits body of with the addition of 175 g dregs palm and without coconut fiber that is 19 fruit, , While most optimum on wet weight with the addition of coconut fiber 350 g and dregs palm 125 g of crop 180g.